Poskeswa in Sidorejo Sukorejo Ponorogo case study: ODGJ income growth through innovation in doormat production - Artadi , Mahira Wijaya Bekti; Wafiroh, Zulva Ni’mal; Febriansyah, Ferry Irawan; Lestari, Wahyu Ikke Siswika (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
People with Mental Disorders (ODGJ) often face stigmatization and barriers to economic participation. Empowering ODGJ through creative activities like doormat production can yield significant social and economic benefits. This study focuses on the village of Sidorejo, which has 41 ODGJ residents. Common perceptions suggest that ODGJ are less productive and unable to engage in meaningful work. This literature review aims to highlight the positive impacts of empowering ODGJ to increase productivity through creative doormat production. The Poskeswa self-help group (SHG) initiative in Sidorejo Village seeks to enhance ODGJ's social and economic abilities. The research examines how empowerment efforts through doormat production can improve ODGJ's income and identifies the positive impacts of these programs. Secondary data were collected from SHG reports at the Sidorejo Health Post and interviews with the village midwife. The study reveals that community development programs provide ODGJ with individual and group counseling, often utilizing sign language for effective communication. The findings indicate that with proper support, ODGJ in Sidorejo Village can acquire life skills that enable them to be self-sufficient, secure employment, and be creative. Consequently, they can generate an income that meets their daily needs, thereby improving their overall quality of life. This research underscores the importance of targeted community development programs in transforming the lives of marginalized groups like ODGJ.